Partial characterization of an isometric virus causing sunflower necrosis disease - K. PRABHAKAR and A. VARMA, M. RAMIAH, A.I. BHAT, R.K. JAlN*, R.P. PANT, Y.S. AHLAWAT, (Indian Phytopathology, 2002)
An isometric virus was established as the causal agent of necrosis disease of sunflower. The virus was purified from cowpea and identified by host range, particle morphology and infectivity test. The virus induced necrosis on leaves foUowed by necrosis on petioles, stems and floral calyx on sunflower cv. Morden upon mechanical inoculation from purified preparation. The exact identity of the virus remains to be determined.